Magnets Assisted Triboelectric Nanogenerator for Harvesting Water Wave Energy. Issue 9 (18th May 2022) - Ouyang, Ri; Miao, Juan; Wu, Tao; Chen, Jiajia; Sun, Chengfu; Chu, Jing; Chen, Dingming; Li, Xin; Xue, Hao
Abstract: Developing renewable energies, especially ocean wave energy, is very significant for solving the energy and environmental crisis. The emergence of triboelectric nanogenerators (TENGs) provides new possibilities for harvesting the abundant clean ocean wave energy on earth. In this work, the magnets assisted triboelectric nanogenerator (MA‐TENG) is designed to harvest low frequency ocean wave energy. The integration of electromagnetic generators (EMGs) and TENGs in the MA‐TENG can accomplish their complementary strengths. Additionally, the MA‐TENG system features four output units and a contact separation structure to further improve its output performance while avoiding friction loss. Driven by the linear motor and simulated water waves, the MA‐TENG system can achieve a maximum power density of 79 and 26.2 W m ‐3, respectively. This research not only demonstrates a new design idea for TENGs, but also provides a cost‐efficient way for wave energy harvesting. Abstract : Here, the magnets assisted triboelectric nanogenerator (MA‐TENG) is designed to harvest low frequency ocean wave energy. The integration of electromagnetic generators (EMGs) and TENGs in the MA‐TENG can accomplish their complementary strengths, providing a cost‐efficient way for blue energy harvesting.